Hot Topics in Pneumologia Interventistica - Volume 2 - Corbetta, Lorenzo (Strumenti per la didattica e la ricerca, 2018)
The Master in Interventional Pulmonology aims at training a versatile pulmonologist, with professional skills in diagnostic and operative bronchoscopy, thoracoscopy and artificial respiratory tracts management with the synergistic contribution of university and hospital teachers. Every year, several specialists from all over the national territory take part to the Master. This work is a collection of all the dissertations presented by the attendants of the seventh edition of the Master in Interventional Pulmonology of the academic year 2015/2016, and acts as evidence and worthy conclusion for a demanding but fruitful year of study and practical activities aimed at certifying professional competence, which can be useful and expendable in the curriculum of a pulmonologist.